The impact of Angiotensin II Type 1 Receptor antibodies on morbidity and mortality in Heart Mate II supported recipients - Urban, Marian; Slavčev, Antonij; Gazdič, Tomáš; Ivak, Peter; Netuka, Ivan (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2016)
AIMS: One of the proposed limitations of left ventricular assist device (LVAD) therapy is high degree of sensitization. Apart from human leukocyte antigen (HLA), antibodies against Angiotensin II Type 1 Receptor (AT1R) have been associated with adverse outcomes. The purpose of this study was to compare complications and survival of anti - AT1R positive versus negative Heart Mate II (HMII) recipients. METHODS: Altogether 96 patients received HMII at our institution between 2008 and 2012. These were stratified into three groups: antibody positive before implantation (AT1R+), antibody conversion during support (AT1R-/+) and patients who remained antibody negative (AT1R-). Survival, major on-device adverse events and post-transplant rejections were assessed with Kaplan-Meier and log-rank tests. RESULTS: Two year on-device and overall survival was 78 ± 12% and 75 ± 10% in AT1R-, 60 ± 23% and 60 ± 15% in AT1R+ and 92 ± 6% and 87 ± 5% in AT1R-/+ group (P = 0.409, P = 0.185). Freedom from major adverse event at two years for AT1R-, AT1R+ and AT1R-/+ was 49 ± 14%, 53 ± 16% and 41 ± 11% (P = 0.875). Freedom from rejection was 63 ± 17% in patients who were both anti-AT1R and HLA negative and 65 ± 13% in those who were antibody positive (P = 0.788). CONCLUSION: Patients who were anti-AT1R antibody positive had similar on-device survival and rate of complications in comparison to those who were antibody negative. In transplanted patients, there were no differences in the overall survival and rejection between the groups.
Keywords: Transplantation Immunology; srdeční selhání; transplantace srdce; Male; Female; Antibodies; HLA Antigens; Middle Aged; nemoci nervového systému; Prosthesis Failure; Prosthesis-Related Infections; protilátky; Heart Failure; transplantační imunologie; mužské pohlaví; Receptor, Angiotensin, Type 1; ženské pohlaví; Adult; Graft Rejection; pooperační krvácení; infekce spojené s protézou; Postoperative Hemorrhage; dospělí; lidé středního věku; selhání protézy; receptor angiotensinu typ 1; rejekce štěpu; Nervous System Diseases; podpůrné srdeční systémy; lidé; Heart Transplantation; Humans; Heart-Assist Devices; HLA antigeny